Prevalence and clinical significance of fetal tricuspid regurgitation during the third trimester of pregnancy - Lopes,Karina Reis de Melo (2021)
Abstract Objectives: the aim of this study was to determine the prevalence of fetal tricuspid valve regurgitation (TR) during the third trimester of low-risk pregnancies and to assess its clinical significance on neonates. Methods: this is a cross-sectional study including 330 singleton fetuses referred for routine fetal echocardiography during 3rd trimester in a fetal medicine center in Recife, Brazil. The presence and degree of tricuspid regurgitation were analyzed. Whenever TR was identified on fetal echocardiography, postnatal data, including the results of postnatal echocardiography were reviewed. Results: the prevalence of tricuspid regurgitation was 10.0% (n=33) in the study population. Regarding regurgitation degree, 90.9% (n=30) presented mild regurgitation and none presented important TR. Postnatal data was obtained from 21 neonates. Twenty of them were discharged without any complications, and one presented respiratory distress due to prematurity. Transthoracic echocardiography was performed in 66.7% (n=14) of the neonates and it was normal in 92.9% (n=13) of them. One neonate, 7.1%, persisted with tricuspid regurgitation, but had no other findings. Conclusions: tricuspid regurgitation in fetuses with normal cardiac anatomy during the 3rd trimester is a common condition in low-risk pregnancies, and is not associated with cardiac abnormalities or need for neonatal intervention.